Optics and Spectroscopy for Fluid Characterization - Johannes Kiefer (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
All over the world, there is a huge and ever-increasing interest in the development and application of optical and spectroscopic techniques to characterize fluids in engineering and science. The large number of review articles that are frequently published in these areas is evidence of this. Recent examples have focused on applications of optical diagnostics to gas phase environments, liquids, and multiphase systems. A key feature of such light-based methods is that they are usually non-intrusive, and hence they do not notably affect the system under investigation. As a consequence, optical techniques have been developed for many decades and represent the gold standard in many fields. The list of individual techniques utilizing absorption, refraction, diffraction and scattering effects is long and so is the list of the parameters that can be determined. The latter includes macroscopic properties such as temperature, chemical composition, thermophysical quantities, and flow velocity, but molecular information, e.g., about isomerism and intermolecular interactions, can also be obtained. This Special Issue entitled "Optics and Spectroscopy for Fluid Characterization" aims to demonstrate the breadth of the field in terms of methodology, as well as applications.